"تأثير الذكاء الإصطناعي في الاعمال القانونية للإدارة العامة " دراسة تحليلية - Mohammed, Rawsht mohammed Ameen; Fars, Ruqia Othman (Journal of Legal and Political Studies, 2025)
The world is witnessing a radical transformation across all sectors thanks to the rapid advancement of artificial intelligence (AI) technologies. Public administration is among the most prominent fields that have begun adopting these technologies to enhance their legal operations, particularly in administrative decision-making and the preparation and conclusion of administrative contracts. This research aims to explore the profound impact of AI on the legal activities of public administration, focusing on its applications in decision-making processes and contract review, and analyzing the benefits and challenges arising from this digital transformation. Keywords: Artificial intelligence, Legal Work of Public Administration (electronic administrative decision - electronic administrative contract), public administration
Keywords: Keywords Artificial intelligence; Legal Work of Public Administration (electronic administrative decision electronic administrative contract); public administration